Historiography of Hadith Writing during the Era of the Companions and the Tabi'in - Abdi Al-Maududi; Bayu Prasetyo; Hisan Arisy (El-Sunnah)
This research examines the historiography of hadith writing during the period of the Companions and the Tabi'in. The method used is a literature study with a descriptive qualitative approach. The results showed that during this period, the understanding and writing of hadith among Muslims were still limited. The Companions received the traditions directly from the Prophet and recorded them, but the number of Companions who were able to write was very small, so the records of the traditions were limited. Moreover, the main focus of the Companions was to preserve the Qur'an so the records of the traditions were found only in the sahifahs owned by the Companions. The method of hadith transmission was also different between the time of the Prophet and the time of Khulafa' al-Rashidin. During the time of the Khulafa' al-Rashidin, there was a simplification in the transmission of traditions, with the requirement that the narrator must swear an oath or present witnesses to confirm the truthfulness of the traditions they conveyed. Meanwhile, during the time of the Tabi'in and Tabi'in al-Tabi'in, there was a compilation of traditions, although sometimes there was still a mixture of the Prophet's traditions, the sayings of the Companions, and the fatwas of the Tabi'in.